Bimodal regulation of the PRC2 complex by USP7 underlies tumorigenesis. Issue 8 (13th April 2021) - Su, Dongxue; Wang, Wenjuan; Hou, Yongqiang; Wang, Liyong; Yi, Xianfu; Cao, Cheng; Wang, Yuejiao; Gao, Huan; Wang, Yue; Yang, Chao; Liu, Beibei; Chen, Xing; et al.
Abstract: Although overexpression of EZH2, a catalytic subunit of the polycomb repressive complex 2 (PRC2), is an eminent feature of various cancers, the regulation of its abundance and function remains insufficiently understood. We report here that the PRC2 complex is physically associated with ubiquitin-specific protease USP7 in cancer cells where USP7 acts to deubiquitinate and stabilize EZH2. Interestingly, we found that USP7-catalyzed H2BK120ub1 deubiquitination is a prerequisite for chromatin loading of PRC2 thus H3K27 trimethylation, and this process is not affected by H2AK119 ubiquitination catalyzed by PRC1. Genome-wide analysis of the transcriptional targets of the USP7/PRC2 complex identified a cohort of genes including FOXO1 that are involved in cell growth and proliferation. We demonstrated that the USP7/PRC2 complex drives cancer cell proliferation and tumorigenesis in vitro and in vivo . We showed that the expression of both USP7 and EZH2 elevates during tumor progression, corresponding to a diminished FOXO1 expression, and the level of the expression of USP7 and EZH2 strongly correlates with histological grades and prognosis of tumor patients. These results reveal a dual role for USP7 in the regulation of the abundance and function of EZH2, supporting the pursuit of USP7 as a therapeutic target for cancer intervention.